Phytochemical analysis and proximate composition of Vernonia amygdalina - Usunobun, Usunomena; Ngozi, Okolie (International Journal of Scientific World, 2016)
Background: Vernonia amygdalina is used to prepare dishes as well as a multi-purpose fodder tree with high biomass yield. This study was conducted to determine phytochemicals and proximate composition of Vernonia amygdalina leaves.Methods: Evaluation of Vernonia amygdalina for phytochemicals and proximate composition were conducted using standard methods.Results: Result showed that Vernonia amygdalina contain phytochemicals such as alkaloids, tannins, flavonoids, saponins, triterpenoids, steroids, cardiac glycosides, and reducing sugar. Results obtained on the proximate composition shows that Vernonia amygdalina in percentage (%) contain dry matter (90.68 ± 0.77), crude protein (22.81 ± 0.17), crude fiber (18.17±0.06), moisture (9.32 ± 0.67), ash (16.65 ± 0.09), crude fat (4.34 ± 0.04) and carbohydrate (38.03 ± 0.06).Conclusion: The presence of phytochemicals like saponins, tannins, alkaloids and flavonoids explains the medicinal potentials of Vernonia amygdalina leaves in therapeutic uses. Also the leafy vegetables if consume in sufficient amount would contribute greatly to the nutritional requirement for human health and to the food security of Nigerian population.